Calcium antagonists use and its association with lower urinary tract symptoms: A cross-sectional study - Elhebir, Elsamaul; Hughes, Jeffery; Hilmi, Samantha (Public Library of Science, 2013)
Background Lower urinary tract symptoms (LUTS) have been reported amongst the side effects of calcium antagonists (CA). CAs act on the bladder by affecting the ability of the detrusor muscle to create enough contractile force to overcome obstruction to normal voiding. We aimed to determine the relationship between CA use and LUTS in general medical inpatients. Methods and Findings In this cross-sectional study we recruited 278 medical inpatients (including 85 CA users) aged ≥40 (72.1±13.7) years. LUTS was assessed using the International Prostate Symptoms Score (IPSS) questionnaire. A Logistic regression model using a ‘backwards-elimination’ strategy was used to identify variables associated with LUTS and for calculating the adjusted odds ratios and the 95% confidence intervals (CI). After adjusting for other risk factors and drugs, patients on amlodipine/nifedipine and diltiazem/verapamil (compared to non-users) were more likely to suffer from severe LUTS [Males: 12.45(CI: 1.57–98.63) and Females: 7.75(CI: 0.94–63.94)] and moderate-to-severe LUTS [Males: 17.43(CI: 2•26–134.39) and Females: 47.8(CI: 6.22–367.37)]. Patients on felodipine/lercanidipine were less likely to suffer from either severe or moderate-to-severe LUTS. Further, 19 (22.4%) CA-users were on treatment for LUTS compared to 18 (9.3%) of the non-users group, p = 0.003. Both male and female CA-users were three times more likely to be on alpha-blockers than non-users, p<0.001. CA-users were more likely to have undergone urinary tract-related surgery (Males: two times, p = 0.07 and females: nine times, p = 0.029). The study was limited by the fact that a causal relationship could not be established between CA use and LUTS. Conclusions Our results demonstrate an association between CA use and an increasing severity of LUTS. They also demonstrate that CA-users are more likely to have medical or surgical treatment for LUTS. However, these CA’s effects on LUTS vary, and the use of highly vascular selective agents does not appear to pose significant risk.